Mapping corpus callosum surface reduction in fetal alcohol spectrum disorders with sulci and connectivity-based parcellation - Fraize, Justine; Convert, Gabrielle; Leprince, Yann; Sylvestre-Marconville, Florent; Kerdreux, Eliot; Auzias, Guillaume; Lefèvre, Julien; Delorme, Richard; Elmaleh-Bergès, Monique; Hertz-Pannier, Lucie; Germanaud, David (Frontiers in Neuroscience, 2023)
Introduction Fetal alcohol spectrum disorders (FASD) range from fetal alcohol syndrome (FAS) to non-syndromic non-specific forms (NS-FASD) that are still underdiagnosed and could benefit from new neuroanatomical markers. The main neuroanatomical manifestation of prenatal alcohol exposure developmental toxicity is the reduction in brain size, but repeated imaging observations have long driven attention on the corpus callosum (CC), without being all convergent. Our study proposed a new segmentation of the CC that relies both on a sulci-based cortical segmentation and on the “hemispherotopic” organization of the transcallosal fibers. Methods We collected a monocentric series of 37 subjects with FAS, 28 with NS-FASD and 38 with typical development (6 to 25y-o), with brain MRI (1.5T). Associating T1- and diffusion-weighted imaging, we projected a sulci-based cortical segmentation of the hemispheres on the midsagittal section of the CC, resulting in 7 homologous anterior-posterior parcels (frontopolar, anterior and posterior prefrontal, precentral, postcentral, parietal, and occipital). We measured the effect of FASD on the callosal and cortical parcels area considering age, sex, and brain size as linear covariates. The surface proportion of the corresponding cortical parcel was introduced as an additional covariate. We performed a normative analysis to identify subjects with an abnormally small parcel. Results All callosal and cortical parcels were smaller in the FASD group compared to controls. When accounting for age, sex and brain size, only the postcentral (η²=6.5%, pFDR=0.032) callosal parcel and % of cortical parcel (η²=8.9%, pFDR=0.007) were still smaller. Adding the surface proportion (%) of the corresponding cortical parcel to the model, only the occipital parcel was persistently reduced in the FASD group (η²=5.7%, pFDR=0.014). In the normative analysis, we found an excess of subjects with FASD with abnormally small precentral and postcentral (peri-isthmic) and posterior-splenial parcels (pFDR<0.05). Conclusion The objective sulcal and connectivity-based method of CC parcellation proved useful in confirming posterior-splenial damage in FASD, but also a narrowing of the peri-isthmic region strongly associated with a specific size reduction in the corresponding postcentral cortical region (postcentral gyrus). Normative analysis showed that this type of callosal segmentation could provide a clinically relevant neuroanatomical endophenotype, even in NS-FASD.